Cross-Cultural adaption, validity and reliability of a Hindi version of the Corah's Dental Anxiety Scale - Meena Jain; Shourya Tandon; Ankur Sharma; Vishal Jain; Nisha Rani Yadav (Tabriz University of Medical Sciences, 2018)
Background: An appropriate scale to assess the dental anxiety of Hindi speaking population is lacking. This study, therefore, aims to evaluate the psychometric properties of Hindi version of one of the oldest dental anxiety scale, Corah's Dental Anxiety Scale (CDAS) in Hindi speaking Indian adults.Methods: A total of 348 subjects from the outpatient department of a dental hospital in Indiaparticipated in this cross-sectional study. The scale was cross-culturally adapted by forward and backward translation, committee review and pretesting method. The construct validity of the translated scale was explored with exploratory factor analysis. The correlation of the Hindi version of CDAS with visual analogue scale (VAS) was used to measure the convergent validity.Reliability was assessed through calculations of Cronbach's alpha and intra class correlation 48 forms were completed for test-retest.Results: Prevalence of dental anxiety in the sample within the age range of 18-80 years was 85.63% [95% CI: 0.815-0.891]. The response rate was 100 %. Kaiser-Meyer-Olkin (KMO) test value was 0.776. After factor analysis, a single factor (dental anxiety) was obtained with 4 items.The single factor model explained 61% variance. Pearson correlation coefficient between CDASand VAS was 0.494. Test-retest showed the Cronbach's alpha value of 0.814. The test-retest intraclass correlation coefficient of the total CDAS score was 0.881 [95% CI: 0.318-0.554].Conclusion: Hindi version of CDAS is a valid and reliable scale to assess dental anxiety in Hindi speaking population. Convergent validity is well recognized but discriminant validity is limited and requires further study.